Evaluation of Poor Standards Implementation in Sorong City - Evi Mufrihah Zain; Indri Handayani; Rais Dera Pua Rawi (International Ecsis Association, 2023)
The purpose of this study is to determine the results of the assessment of poor standards by the Central Statistics Agency (BPS) of Sorong City. This research uses a descriptive method with a qualitative approach. The population in this study consisted of BPS Sorong City staff and Sorong City residents who came from slums. The sampling technique uses purposive sampling with the criteria of BPS Sorong City employees who are qualified to collect information on poor people and community leaders who have information (data). Data collection techniques use observation, interviews, literature review, and documentation with data collection, data reduction, and data presentation. Data analysis techniques use source triangulation. The results show that BPS's poverty criteria standard is considered less effective as a guideline for determining poor people. Because they use the same criteria from year to year and do not pay attention for a long time, moreover the criteria also apply to all of Indonesia, with BPS ignoring the different characteristics of poverty in each region in Indonesia.